2022
DOI: 10.21931/rb/2022.07.02.44
|View full text |Cite
|
Sign up to set email alerts
|

Identification of methicillin-resistant strains of Staphylococcus aureus isolated from humans and food sources by use mecA 1 and mecA 2 genes in Pulsed-field gel electrophoresis technique

Abstract: Staphylococcus aureus causes mastitis in dairy cows, lambs, goats, and skin disorders in pigs and other animals. S. aureus causes localized purulent infections that affect soft tissues, bones, and other organs in humans. Using restriction patterns, the researchers want to isolate and identify methicillin-resistant Staphylococcus aureus (MRSA) strains from cattle and humans. They also hope to assess their genetic relatedness by comparing the mecA1 and mecA2 gene sequence discrepancies. Animals (223 strains) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…Recently, cancer disease can be diagnosed by PCR, such as CML 34 and Adenocarcinoma 35,36 . This molecular technique was also employed to diagnosis different microorganisms that caused pathogenicity in human such as Clostridium perfringens 37 , Brucella melitensis 38 , Proteus vulgaris 39,40 , Staphylococcus aureus 41 , Pseudomonas aeruginosa 42,43 , and Toxoplasma spp 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cancer disease can be diagnosed by PCR, such as CML 34 and Adenocarcinoma 35,36 . This molecular technique was also employed to diagnosis different microorganisms that caused pathogenicity in human such as Clostridium perfringens 37 , Brucella melitensis 38 , Proteus vulgaris 39,40 , Staphylococcus aureus 41 , Pseudomonas aeruginosa 42,43 , and Toxoplasma spp 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports and agrees with earlier studies that found lower serum lipid profile levels in diabetic mice (14), lower serum total cholesterol levels in Wistar rats (15) and reduced total cholesterol levels in chamomile diet-induced rats (16). As a result of the information that has been provided thus far, we recommend that chamomile extract be evaluated for use in biological chemistry as well as a variety of medicinal applications, including the treatment of cancer may be recommended to treat CML (17), Adenocarcinoma (18), and the prevention of a wide range of pathogenic bacteria, viruses, and parasites such as Clostridium perfringens (19), Brucella melitensis (20), Proteus vulgaris (21), Staphylococcus aureus (22), Pseudomonas aeruginosa (23), and Toxoplasma spp (24,25), SARS-Cov-2 (26).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the size of the sample will provide results that are easier to distinguish in terms of the effect that the ACE-2 gene has on COVID-19. The molecular approach was used to diagnose many pathogens, including : Proteus vulgaris, 31,32 Clostridium perfringens, 33 Staphylococcus auras, 34,35,36 Brucella melitensis, 37 Pseudomonas spp, 38 Toxoplasma spp 39,40 and SARS-Cov-2. 41,42 Also, Chronic Myeloid Leukemia, 43 Adenocarcinoma, 44,45 and another cancers 46 ,were considered severe genetic illnesses and diagnostic by PCR was suggested.…”
Section: Frequency and Distribution Of Ace-2 Gene Polymorphism And Su...mentioning
confidence: 99%